Association of tissue lymphocyte immunophenotype and clinical outcomes: A prospective study in patients with ulcerative colitis treated with vedolizumab - Katsuyoshi Ando; Shin Kashima; Aki Sakatani; Hiroaki Konishi; Atsuo Maemoto; Takahiro Ito; Masaki Taruishi; Kenichi Hamagami; Kaori Ishiguro; Mikihiro Fujiya (PLoS ONE, 2026)
Introduction Vedolizumab binds to α4β7 integrin, thereby inhibiting lymphocyte migration into the gastrointestinal tract. It is used to treat moderate to severe ulcerative colitis (UC) and Crohn’s disease. This study evaluated vedolizumab concentrations, α4β7 integrin saturation, and T lymphocyte immunophenotype proportions in blood, serum and inflamed colorectal tissue according to treatment efficacy in patients with moderate to severe UC. Methods This was a phase 4, multicenter, open-label, single-arm study. Patients were observed for a total of 54 weeks. Clinical remission was defined as complete Mayo score ≤ 2 or partial Mayo score ≤ 1. Results The study included 11 patients with UC, 10 of whom were tumor necrosis factor alpha antagonist therapy-naïve. Seven and six patients were in remission at weeks 14 and 54, respectively. Vedolizumab concentrations and lymphocyte α4β7 integrin saturation in serum and inflamed colorectal tissue at weeks 14 and 54 did not differ significantly between remitters and non-remitters. The proportion of T cell subsets differed in remitters and non-remitters for CD4 + T cells in blood at week 14 (62.7% vs 47.4%, p = 0.0061) and CD161 + memory CD4 + T cells (65.7% vs 53.1%, p = 0.0357) in inflamed colorectal tissue at week 54. Week 54 remitters had higher proportions of CD161 + memory CD4 + T cells in inflamed colorectal tissue at baseline (before vedolizumab treatment) than did week 54 non-remitters (48.5% vs 31.3%, p = 0.0303). Conclusion T cell immunophenotype may be a promising predictive biomarker of vedolizumab treatment efficacy.